1999
DOI: 10.1152/ajpregu.1999.276.3.r864
|View full text |Cite
|
Sign up to set email alerts
|

Role of central melanocortins in endotoxin-induced anorexia

Abstract: Inflammation and microbial infection produce symptoms, including fever, anorexia, and hypoactivity, that are thought to be mediated by endogenous proinflammatory cytokines. Melanocortins are known to act centrally to suppress effects on fever and other sequelae of proinflammatory cytokine actions in the central nervous system, but the roles of melanocortins in anorexia and hypoactivity occurring during the acute phase response are unknown. The present study was designed to determine the effects of exogenous an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
95
2
5

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(111 citation statements)
references
References 27 publications
9
95
2
5
Order By: Relevance
“…The current results show that pretreatment with the melanocortin antagonist blocked this reduction in activity. Decreased activity in response to IL-1β is consistent with reports in the literature (Morgan et al, 2004;Wieczorek and Dunn, 2006) and a consistent response to peripheral immune activation (e.g., LPS (Huang et al, 1999)). It has been reported that nonselective blockade of melanocortin receptors with the drug SHU9119 did not ameliorate LPS-induced hypoactivity and had no effect on its own (Huang et al, 1999).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The current results show that pretreatment with the melanocortin antagonist blocked this reduction in activity. Decreased activity in response to IL-1β is consistent with reports in the literature (Morgan et al, 2004;Wieczorek and Dunn, 2006) and a consistent response to peripheral immune activation (e.g., LPS (Huang et al, 1999)). It has been reported that nonselective blockade of melanocortin receptors with the drug SHU9119 did not ameliorate LPS-induced hypoactivity and had no effect on its own (Huang et al, 1999).…”
Section: Discussionsupporting
confidence: 90%
“…Decreased activity in response to IL-1β is consistent with reports in the literature (Morgan et al, 2004;Wieczorek and Dunn, 2006) and a consistent response to peripheral immune activation (e.g., LPS (Huang et al, 1999)). It has been reported that nonselective blockade of melanocortin receptors with the drug SHU9119 did not ameliorate LPS-induced hypoactivity and had no effect on its own (Huang et al, 1999). However, this study used different drugs (SH9119 and LPS) than the current study and a different experimental design (the SHU9119 was given 30 after LPS administration (as opposed to 15 min pretreatment in the current studies) and the injections were given in the early lights on period (as opposed to at the onset of lights off)), which likely contribute to the differing results.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Mc4r are involved in the anorexia associated with lipopolysaccaride and tumor-induced cachexia [20,25,27,35,36]. To determine if antagonism of Mc4r by PG932 can attenuate illness behavior, we assessed food intake and spontaneous physical activity of mice treated with LPS (Fig.…”
Section: Peripheral Injections Of Pg932 Transiently Reduce Anorexia Amentioning
confidence: 99%
“…It has been already demonstrated that the activation of POMC neurons promotes the release of -melanocyte stimulating hormone ( -MSH), which, in turn, activates melanocortin 4 receptor (MC4R) (Cone, 2005). Melanocortin has been also implicated in the LPS-induced hypophagia, since the administration of exogenous -MSH intensified, whereas the antagonism of MC4R attenuated the inhibitory effect of LPS on food intake (Fan et al, 1997;Huang et al, 1999). Within this context, glucocorticoids appear as negative regulators of melanocortin signaling, since ADX was shown not only to reduce AgRP expression in the hypothalamus of wild type mice, but also to reverse obese phenotype and restore hypothalamic melanocortin tone to control levels in leptin-deficient ob/ob mice (Makimura et al, 2000).…”
Section: Glucocorticoids In the Interface Of Immune Challenges And Fomentioning
confidence: 99%